Studi Perlindungan Sosial yang Adaptif dan Berkemampuan Bagi Pekerja di Masa Pandemi COVID-19 - Henriko Tobing (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2023)
The impact of several crises on health, economy, and crisis caused by technological development upon workers resulted in three cases: 1) wage reduction, 2) Layoff or employment degradation, and 3) limited social security, particularly for vulnerable workers. Therefore, To anticipate this issue, an adaptive social security policy is needed for any crisis form and payment coverage. Social security programs in Indonesia are considered enough to comprehend employment protection, including employers. In contrast, these types of programs can be categorized as social security programs which are classified as adaptive. In reality, problems still occur here and there, mainly entry-related and benefit value. Considering the Nation's ability to finance social security programs with limited contribution, therefore, to create competent social security, a social contribution mechanism (companies-employe and Government) is needed to ensure continuation. Massive socialization with the involvement of every people's component as well as law enforcer toward social security provision provided a successful way to increase participant's scope to become an essential aspect of creating continuous social security financing.